Neuroprotective effects of potassium channel openers on cerebral ischemia-reperfusion injury in diabetic rats - Anand B. Pithadia; Shital S. Panchal; Denvanshu J. Patel (Faculty of Pharmacy, Cairo University, 2017)
Objectives: This study was done to estimate the potential neuroprotective role of potassium channel openers in cerebral ischemia-reperfusion (IR) injury in streptozotocin (STZ) induced type-I diabetic rats (T1DR). Methods: Potassium channel openers - cromakalim, cinnarizine and nicorandil; potassium channel blocker -glibenclamide, insulin (as an antidiabetic standard), telmisartan (as an anti-hypertensive standard agent) and vitamin E (as an antioxidant and antiapoptotic standard agent) were given for 3 days in streptozotocin (45 mg/kg i.v.) induced type I diabetic rats along with middle cerebral artery occlusion. After 24 h of surgery, plasma glucose, neurobehavioral score, cerebral infarct volume, blood pressure and caspase-3 levels were measured to evaluate the mechanism of potassium channel openers (KCOs) for neuroprotection. Results: Following STZ administration and ischemia-reperfusion, blood sugar, neurobehavioral score, cerebral infarct volume and caspase-3 levels were significantly high in diabetic-IR groups. Treatment with cromakalim, cinnarizine, nicorandil, insulin and vitamin E significantly reduce neurobehavioral score while nicorandil and vitamin E significantly reduced cerebral infarct volume. Caspase-3 levels were significantly reduced by cromakalim and nicorandil treated animals. Except insulin and glibenclamide, none of the agents significantly reduce plasma glucose levels. Conclusion: Treatment of ischemic stroke with potassium channel openers in T1DR is neuroprotective. Inhibition of apoptosis may contribute to their neuroprotective effects after stroke in T1DR.